Living Hadith in the Peu Intat Ritual: Sacredness and Cultural Adaptation in the Death Tradition of the Teunom Community, Aceh Jaya - M. Jakfar, Tarmizi (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2024)
The Peu Intat ritual in the Teunom community of Aceh Jaya represents a localized form of Living Hadith, where prophetic traditions are actively preserved and practiced within a socio-cultural framework. This study examines Peu Intat as an applied interpretation of hadith and explores its social, theological, and cultural functions. Using a qualitative approach with the Living Hadith framework, data were collected through interviews, participant observation, and document analysis involving religious scholars, community leaders, and local residents. The findings reveal that Peu Intat serves three key functions: (1) strengthening community and familial solidarity, (2) reinforcing faith by guiding the dying person to recite kalimat tauhid, and (3) integrating hadith into local traditions, reflecting the adaptability of Islamic teachings. This study confirms that Living Hadith is not merely textual transmission but a dynamic process shaped by local contexts.